Game Website-Based English Learning Developed for Elementary School Students in Fourth Grade - Ni Luh Kadek, Erna Wijayani; Nitiasih, Putu Kerti; Budiarta, Luh Gd. Rahayu (Jurnal Pendidikan Bahasa Inggris undiksha, 2022)
There are lots of schools in Indonesia still use conventional learning method in learning process. That is still using the book as a medium of learning. Learning media used in the 4.0 era is still minimal and rarely uses technology as a learning medium. Gamification can be used as an alternative learning media that can make the learning process more effective, engaging, and fun. This research aims to develop learning media in the form of game for elementary school students' in learning English. This study uses a design and development (D&D) methodology and the ADDIE model. The research subject is the fourth-grade elementary school students. The instrument used was a questionnaire and observations. And the data analysis used is descriptive qualitative and descriptive quantitative.  The resulting data are in the form of (1) the design and development results using the ADDIE method (analysis, design, development, implementation, and evaluation). (2) To obtain product validity and effectiveness results from expert judgment, teacher, and product trial to students. From the results of expert judgment, very valid results were obtained. And the students' results are very valid, and several things need to be revised again to perfect the product